PERBANDINGAN SYARAT MUTU FISIKA SEMEN PPC DENGAN SEMEN MORTAR (LEM BATA RINGAN) - Dwi Deshariyanto; Anita Intan Nura Diana; Subaidillah Fansuri (Fakultas Teknik, Universitas Wiraraja, 2022)
Light brick in its implementation is done installation using lightweight brick adhesive, but in various places, especially in the Sumenep district installation of lightweight bricks using ordinary cement or widely circulated in the market such as PPC cement. Based on these differences this study will compare the physical quality requirements between PPC cement with cement mortar (lightweight brick glue) in the Sumenep district. The purpose of the study comparing the physical quality requirements of PPC cement with cement mortar (light brick glue) is to determine the binding time, decline or hardening and compressive strength between PPC cement and cement mortar (light brick glue). This research is an experimental research. Test objects for the binding time and hardening of both PPC cement and cement mortar (light brick glue) by making pasta balls, while test objects for compressive strength by making 5 x 5 x 5 cm cube-shaped test objects. PPC cement showed a decrease at 105 minutes by 4.1 mm and the initial bonding time occurred at 139 minutes with a penetration of 25 mm. PPC cement meets the physical requirements of SNI. Cement mortar (lightweight brick glue) for 150 minutes did not decrease and harden at all, so the initial bonding time of cement mortar (lightweight brick glue) meets the SNI requirements. The compressive strength of PPC cement has an average compressive strength of 26.33 MPa, while cement mortar (lightweight brick glue) is 4 MPa. The compressive strength of PPC cement meets the SNI requirements, while cement mortar (lightweight brick glue) does not meet the SNI requirements. Cement mortar (lightweight brick glue) is more appropriate to use in the implementation of lightweight brick installation and PPC cement is stronger when compared to cement mortar (lightweight brick glue).